Juridical Analysis of Maladministration in Public Healthcare Facilities - U.Gultom; V.Pardede (International Medical Journal Corp. Ltd, 2025)
Introduction: Public healthcare facilities serve as the cornerstone of state-sponsored welfare, yet they are frequently plagued by maladministration that compromises patient rights and institutional integrity. This study addresses the systemic failure of administrative duties within public clinics and hospitals, where procedural deviations often lead to severe legal and ethical lapses. Methods: Using a normative juridical research method, this paper examines statutory frameworks, ministerial regulations, and public ombudsman reports to map regulatory gaps. Results: The analysis reveals that maladministration primarily manifests as protracted delays, unauthorized fee collections, and blatant deviations from established standard operating procedures. These issues are exacerbated by overlapping regulatory mandates and a profound lack of punitive enforcement mechanisms. Discussion: The discussion deepens the literature review by contextualizing public healthcare accountability within administrative law theories, specifically focusing on the principles of good governance and state responsibility. It evaluates how bureaucratic inertia intersects with medical ethics, illustrating that legal remedies remain inaccessible to vulnerable demographics due to systemic power imbalances. Conclusions: This study concludes that resolving healthcare maladministration requires a comprehensive harmonization of administrative statutes alongside the statutory empowerment of independent oversight bodies. It suggests implementing strict, automated accountability metrics to protect public health interests effectively.